2004
DOI: 10.1212/01.wnl.0000144194.29643.d0
|View full text |Cite
|
Sign up to set email alerts
|

Preferential gray matter involvement in dengue myelitis

Abstract: Dengue virus (DV) belongs to the family Flaviviridae, and its infection is characterized by dengue fever, dengue hemorrhagic fever, and dengue shock syndrome. Some flaviviruses, such as Japanese encephalitis, St. Louis encephalitis, Murray Valley encephalitis, and West Nile viruses, have the common feature of neurovirulence in the human CNS, including poliomyelitis-like syndrome. 1 We report a patient with dengue fever who developed gray matter myelitis.Case report. A 42-year-old Japanese man working in Indone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 5 publications
0
41
1
Order By: Relevance
“…[5][6][7][8] There is only a single case report of myelitis in the postinfectious phase, occurring 16 days after the onset of illness. 9 The pathogenesis of myelitis in our case is likely direct spinal neuronal involvement of the dengue virus, but the exact mechanism is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] There is only a single case report of myelitis in the postinfectious phase, occurring 16 days after the onset of illness. 9 The pathogenesis of myelitis in our case is likely direct spinal neuronal involvement of the dengue virus, but the exact mechanism is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that parainfectious TM is more frequently associated with flaccid paraparesis, whereas postinfectious TM is typically associated with spastic paraparesis. [8][9][10] Other arboviruses can infect the nervous system, causing TM. The emergence or re-emergence of new arboviruses in the Americas as Zika, chikungunya, Mayaro, West Nile, and others, 11,12 highlights the need of the physicians pay more attention to the diagnosis of TM.…”
Section: Introductionmentioning
confidence: 99%
“…However, involvement of spinal cord in association with dengue fever has been occasionally reported. There have been very few reported cases of acute transverse myelitis in association with dengue infection (5)(6)(7)(8) .…”
Section: Introductionmentioning
confidence: 99%